The Effectiveness of Self-Management Techniques in Group Counseling Through Google Meet To Increase Students' Interest in Online Learning During the Covid-19 Pandemic At Dr. High School. Soetomo Surabaya - Yosefina fatima Lisa; Sutijono Sutijono; Dimas Ardika Miftah Farid (Buana Pendidikan, 2021)
The purpose of this study is to determine the effectiveness of cell-management techniques in group counseling through google meet to increase student interest in online learning during the covid-19 pandemic at Dr. Soetomo Surabaya. The experimental method with the One Group Pretest-Postest Design is the method in this study. This study selected five subjects from class X IPS 1 who experienced low and very low category of interest in learning. In this study, it was found that 5 people experienced a very low and very low interest in learning, after the subject went through the treatment into a high and very high category, who experienced a high interest in learning, using the SPSS For Windows T test version 26.0 obtained T test or f = 11.824 on significance level of 0.001 which means significance. Based on the results of this study, self-management techniques in group counseling through Google meet to increase student interest in online learning during the Covid-19 pandemic at Dr. Soetomo Surabaya.